The Relationship of Protein Intake to Creatinine Levels and Blood Pressure in Fitness Member - Myra, Sofhie; Kuswari, Mury; Utami, Dessy Aryanti; Azra, Jeallyza Muthia; Nuzrina, Rachmanida (Nutrition Study Program, Faculty of Medicine, Universitas Negeri Semarang, Indonesia, 2024)
Background: Fitness center members generally eat foods high in protein, reaching 2 grams/kg body weight or more, and are often accompanied by supplements such as creatinine. High protein intake in the long term will produce a metabolic load that can cause impaired kidney function. In addition to creatinine, the influence of high protein intake that individuals with high activity directly feel is Blood Pressure. Objective: This study aims to determine the relationship between protein intake, creatinine levels, and blood pressure in fitness members at Osbond Gym Cempaka Putih. Method: This type of quantitative research uses a cross-sectional design, with a sample of 22 respondents, namely fitness members at Osbond Gym Cempaka Putih. Data analysis was performed using the Pearson correlation test for normally distributed data and the Spearman correlation test for abnormally distributed data. The test criteria are seen if the p-value < 0.05, then Ha is accepted, and Ho is rejected. Test Results in Normality Variables Protein Intake and Type of Exercise are abnormal, and other variables are normal. Results: All respondents (100%) in this study had been on a high-protein diet for over one year. Most respondents were between 26 and 35 (40.9%) and 36-45 years (40.9%). More respondents were men (68.2%). Most respondents did this weight training (81.8%), with an average exercise frequency of 367.73 minutes/week. The average protein intake of respondents was 212.7736 grams/day, the average body mass index was 25.33 kg / m2, and the average creatinine levels of respondents were 1.01 mg / dL. Most respondents had normal systolic (72.7%) and diastolic (68.2%) blood pressures. Conclusions: There was no association between protein intake, BMI, exercise, and creatinine levels. There is a relationship between sex and creatinine levels. There was no association between protein intake, sex, BMI, and exercise with systolic and diastolic blood pressure.